The relevance of chromosome fissions for major ribosomal DNA dispersion in hymenopteran insects - Menezes, Rodolpho S. T.; Cabral-de-Mello, Diogo C. [UNESP]; Milani, Diogo [UNESP]; Bardella, Vanessa B. [UNESP]; Almeida, Eduardo A. B. (Oxford University Press (OUP), 2021)
Ribosomal DNA (rDNA) loci are essential for cellular metabolism due to their participation in ribosome biogenesis. Although these genes have been widely cytogenetically mapped, the evolutionary mechanisms behind their variability in number and chromosomal location remain elusive, even in well-known biological groups, such as ants, bees and wasps (Insecta: Hymenoptera). To address this question in Hymenoptera and therefore advance the understanding of rDNA evolution in insects in general, we integrated molecular cytogenetic data, a phylogenomic framework, model-based predictions and genome sequencing. Hence, we assessed the main evolutionary trends shaping the chromosomal distribution of rDNA loci in Hymenoptera. We noticed the conservation of one site of rDNA per haploid genome, suggesting that a single 45S rDNA locus is the putative ancestral pattern for aculeate Hymenoptera. Moreover, our results highlighted a nonrandom distribution of rDNA in Hymenoptera karyotypes, as well as a lineage-specific preferential location. The proximal location of rDNA is favoured in species with multiple loci and in the two families of Hymenoptera that show the highest range of chromosome numbers: Formicidae and Vespidae. We propose that chromosome fissions have played a crucial role in the distribution pattern of rDNA loci through the evolutionary diversification of Hymenoptera. Moreover, our genomic analysis of two species, one with a single locus of rDNA and one with multiple loci, supported that loci multiplication is followed by sequence divergence. Our results provide detailed information about the number and chromosomal position of rDNA in Hymenoptera and, therefore, broaden our knowledge regarding rDNA evolutionary dynamics in insects.
Keywords: 45S rDNA; Ants; Bees; Chromosomal evolution; molecular cytogenetics; social wasps